Effects of wheat middlings and choice white grease in diets on the growth performance, carcass characteristics, and carcass fat quality in growing-finishing pigs - J A Barnes; Joel M DeRouchey; Michael D Tokach; Robert D Goodband; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2010)
A total of 288 pigs (PIC TR4 x 1050, initially 93.3 lb) were used in an 87-d study to determine the effects of wheat middlings and choice white grease (CWG) on growth performance, carcass characteristics, and carcass fat quality of growing-finishing pigs. Pens of pigs were randomly allotted by initial weight and gender (4 barrows and 4 gilts per pen) to 1 of 6 dietary treatments with 6 replications per treatment. Treatments were arranged in a 2 x 3 factorial arrangement with the main effects of added wheat middlings (0 or 20%) and CWG (0, 2.5, or 5%). Dietary treatments were corn-soybean meal-based diets with 15% dried distillers grains with solubles (DDGS) and fed in 4 phases. There were no CWG x wheat middlings interactions (P ≥0.12) for any of the criteria evaluated. Overall, (d 0 to 87) adding 20% dietary wheat middlings decreased (P<0.001) ADG and worsened (P<0.001) F/G. Pigs fed diets with increased dietary CWG had increased (quadratic, P<0.03) ADG and improved (linear, P<0.01) F/G. Pigs fed diets containing 20% wheat middlings had decreased (P<0.01) final BW; while there was a numerical increase in final BW (P<0.09) as dietary fat was increased. For carcass traits, pigs fed wheat middlings had decreased percentage yield (P<0.04), HCW (P<0.003), backfat depth (P<0.04), and loin depth (P<0.001), while jowl iodine value increased (P<0.001). Additionally, pigs fed added fat had a tendency for increased backfat depth (linear; P<0.06) and had a linear increase (P<0.01) in jowl iodine value. For economics, adding 20% wheat middlings to the diet decreased (P<0.001) feed cost per pig and feed cost per lb gain; however, total revenue was also reduced (P<0.003), resulting in a numeric decrease (P = 0.13) in income over feed cost (IOFC). Adding CWG increased (linear; P<0.001) feed cost per pig and feed cost per lb gain, but only numerically increased (P = 0.12) total revenue, leading to a tendency for decreased IOFC (linear; P<0.09), with increasing amounts of CWG. Therefore, wheat middlings can be used as an alternative ingredient in swine diets to decrease feed cost and feed cost per lb of gain, but in this study the reduced performance resulted in less revenue and lower profitability.; Swine Day, Manhattan, KS, November 18, 2010
Keywords: Swine Day; 2010; Kansas Agricultural Experiment Station contribution; no. 11-016-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1038; Swine; Energy; DDGS; Wheat middlings